2006
DOI: 10.1111/j.1540-8167.2006.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Burden During the Post‐Implant Period After CRT Using Device‐Based Diagnostics

Abstract: (1) Diagnostic features for long-term monitoring of physiological variables provide useful information on the state and course of AF and may improve disease management. (2) AF burden reduces over time during the first 3 months after CRT implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…It should also be noted that the rate of new-onset AT in MADIT-CRT was somewhat lower (8%) than that in prior CRT studies that enrolled patients with more advanced HF symptoms (in which the reported frequency of new-onset AT was between 10% and 30%) (8,14,15,18). Thus, the present findings regarding reduction in the risk of newonset AT/AF among responders to CRT-D therapy pertain only to patients with asymptomatic or mildly symptomatic LV dysfunction.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It should also be noted that the rate of new-onset AT in MADIT-CRT was somewhat lower (8%) than that in prior CRT studies that enrolled patients with more advanced HF symptoms (in which the reported frequency of new-onset AT was between 10% and 30%) (8,14,15,18). Thus, the present findings regarding reduction in the risk of newonset AT/AF among responders to CRT-D therapy pertain only to patients with asymptomatic or mildly symptomatic LV dysfunction.…”
Section: Discussionmentioning
confidence: 85%
“…In the CARE-HF (Cardiac Resynchronization in Heart Failure) trial (14), treatment with CRT was not associated with a significant reduction in the risk of new AF or time to first AF episode compared with best medical therapy in patients with NYHA class III/IV HF. In contrast, Hugl et al (18), in a small study of 84 patients with advanced HF symptoms, showed that the burden of AF was reduced during the first 3 months after CRT implant. This reduction in chronic AF was also accompanied by a significant 50% reduction in the incidence of new-onset AF.…”
Section: Discussionmentioning
confidence: 86%
“…Several studies analyzed device-stored data to assess the incidence of AF in CRT patients [5,[8][9][10][11][12][13][14][15][16][17]. However, in the great majority of them + p < 0.05 vs. group with AF during follow-up; #79 patients survived the 24-month period: 10 with and 69 without AF history prior to cardiac resynchronization therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Modern implantable devices are capable of detecting any, even short-lasting AF episodes and can store numerous arrhythmia-related parameters, like its cumulative load, number of episodes, or ventricular response. Although it has been suggested, that CRT can reduce AF incidence, data on its exact incidence, burden and predisposing factors are still scarce in patients undergoing biventricular pacing [5]. What is more, it is still a subject of controversy which parameters: cumulative time spent in arrhythmia, episode duration or the number of AF episodes have the prognostic significance.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, others similarly reported no effect of CRT of AF burden, although CRT might have delayed onset of new AF [56]. Hügl et al [57] found a gradual reduction of AF burden when CRT was started. This was supported by Yannopoulos et al [58], who noted a decrease in number and duration of atrial tachyarrhythmia episodes 1 year after starting CRT compared with 3 months before CRT.…”
Section: Cardiac Resynchronizationmentioning
confidence: 99%